Pengaruh Kombinasi Clapping dan Suction terhadap Tidal volume pada Pasien Gagal Napas dengan Ventilasi Mekanik - Aldilla Aini Rahma Latifa; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Patients who are admitted to the Intensive Care Unit (ICU) often require mechanical ventilation due to respiratory failure. One of the common problems that arises in patients with mechanical ventilation is the buildup of sputum, which can interfere with the ventilation process as well as lower the tidal volume. To overcome this, a combination of clapping and suction interventions are used as a therapeutic method with the aim of helping to clear the airways and improve ventilation function. This study aims to determine the effect of the combination of clapping and suction on tidal volume in patients with respiratory failure using mechanical ventilation. The research design used a pre-experiment with a one-group pretest-posttest approach on 43 respondents in the ICU room. Interventions in the form of clapping and suction are given in a structured manner according to standard nursing procedures. The results showed that the majority of respondents were female (53.5%), with the most medical diagnosis being SNH (23.3%). Most of the respondents were in the late adult age category (32.6%) and used PCV ventilation mode (51.2%). Before the intervention, most respondents had a low tidal volume (72.1%), while after the intervention the majority had an increase to the normal category (90.7%). The Wilcoxon test showed a value of p = 0.001, which means that there is a significant effect of the combination of clapping and suction on the increase in tidal volume. Thus, it can be concluded that the combination of clapping and suction is an effective intervention in increasing tidal volume in patients with respiratory failure with mechanical ventilation at the ICU of RSI Sultan Agung Semarang.